Comparative Evaluation of Antibacterial Efficacy, Molecular Docking of Ethanolic Extract of Blackseed, Seaweed and Calcium Hydroxide Intracanal Medicament with Enterococcus Faecalis Antigens - Radha S; Gutmann James L; Bhavani S; Rajaraman G; Chittrarasu M (Wolters Kluwer Medknow Publications, 2024)
AimTo evaluate the inhibitory effect of ethanolic extract blackseed, seaweed, and calcium hydroxide intracanal medicament with Enterococcus faecalis biofilm. To study the binding interaction between the active components of blackseed and seaweed against the enterococcal surface protein of (E. faecalis) by molecular docking. Materials and MethodsThe ethanolic extracts of blackseed and seaweed were prepared using the Soxhlet apparatus. They were divided into three groups, namely, |Group I: Calcium hydroxide, Group II: Blackseed, and Group III: Seaweed. The antibacterial activity of the three groups was detected employing various concentrations ranging from 250, 125, and 62.5 μg/ml and based on the zone of inhibition. The inhibitory potential of medicaments to inhibit E. faecalis growth at various stages and kinetics plate were assessed following biofilm architecture evaluation by crystal violet biofilm assay. With the Swissdock suite, the molecular docking procedure was carried out. PyMOL version 4.1.5 was the program used for visualization. Since enterococcal surface protein (Esp) is primarily involved in the formation of biofilms, it was chosen as the target protein of E. faecalis. Based on their chromatographic investigations, Group II Thymoquinone (TQ) and Group III Ledenoxide were chosen as ligands. ResultsThe percentage of inhibition of E. faecalis biofilm was analyzed as statistically significant observed within groups. On post-hoc analysis, significant differences were present between the groups (P < 0.05). Molecular docking reveals binding energies of thymoquinone (Group II) and ledenoxide (Group III) against the enterococcal surface protein of E. faecalis were −6.90 Kcal/mol and −6.44 Kcal/mol, respectively. ConclusionCompared to seaweed, black seed extract exhibited higher antibacterial activity against the E. faecalis biofilm in microbial inhibition and molecular interaction.